2008
DOI: 10.1016/j.jcmg.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Left Ventricular Mass and Geometry Following Myocardial Infarction

Abstract: Increased baseline LV mass and abnormal LV geometry portend an increased risk for morbidity and mortality following high-risk myocardial infarction. Concentric LV hypertrophy carries the greatest risk of adverse cardiovascular events including death. Higher RWT was associated with an increased risk of cardiovascular complications after high-risk myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(99 citation statements)
references
References 34 publications
5
85
2
7
Order By: Relevance
“…However, the findings by Małek et al were limited by a small number of patients (n=52), the lack of multivariable analyses despite important differences in baseline variables between LVH and normotrophic patients, and missing measurements of MVO, area at risk, and salvage index. In contrast to our and previous observations,6 Małek et al did not report any difference in LVEF. The importance of measuring area at risk in addition to infarct size has previously been emphasized given that area at risk has an impact on infarct size 30.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the findings by Małek et al were limited by a small number of patients (n=52), the lack of multivariable analyses despite important differences in baseline variables between LVH and normotrophic patients, and missing measurements of MVO, area at risk, and salvage index. In contrast to our and previous observations,6 Małek et al did not report any difference in LVEF. The importance of measuring area at risk in addition to infarct size has previously been emphasized given that area at risk has an impact on infarct size 30.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the presence of LVH in approximately one third of patients with MI,6 the causal association between LVH and impaired outcome in patients with ST‐segment elevation myocardial infarction (STEMI) remains unknown. Experimental studies have demonstrated that animals with LVH have less myocardial salvage and larger infarct size following ischemia‐reperfusion 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another analysis from 5098 subjects in the Multi‐Ethnic‐Study of Atherosclerosis (MESA) showed LV geometry based on cardiac MRI was a better predictor of stroke and coronary heart disease compared to LV mass alone 22. Similar associations were reported in several other disease populations, such as those with CAD,17 post–myocardial infarction,23 atrial fibrillation,24 hypertension,15, 25, 26, 27, 28 CKD,27 preserved LV function,28, 29, 30 and advanced age 31. However, most recently an analysis among patients with LVEF ≤30% enrolled in the MADIT‐CRT study found the magnitude of eccentric remodeling to be predictive of risk of recurrent ventricular arrhythmias 18.…”
Section: Discussionmentioning
confidence: 66%
“…In that study, the odds ratio for incident cardiovascular disease in patients with concentric LVH compared with those with normal geometry was 1.3 (95% CI, 0.8–2.1) in men and 1.2 (95% CI, 0.6–2.3) in women after controlling for LVM and other cardiovascular risk factors 8. In contrast, LVM and relative wall thickness were independent predictors of all‐cause death, cardiovascular death, and hospitalization for heart failure in patients with acute myocardial infarction included in the VALIANT (Valsartan in Acute Myocardial Infarction) echocardiographic study 29. Partially different findings have been reported by Huang and coworkers in a patient population with coronary artery disease undergoing coronary angiography 30.…”
Section: Discussionmentioning
confidence: 95%